Determinants of Multi‐unit Franchising: An Organizational Economics Framework. (21st December 2012) - Hussain, Dildar; Perrigot, Rozenn; Mignonac, Karim; Akremi, Assâad El; Herrbach, Olivier; Ehrmann, Thomas; Cliquet, Gérard; Hendrikse, George W. J.; Windsperger, Josef
<x xml:space="preserve">Abstract</x> In this paper, we use organizational economics theories to explain the percentage of multi‐unit franchisees within franchise chains. We use transaction cost theory, property rights view and agency theory to formulate three research hypotheses that are related to franchisees' transaction‐specific investments, intangibility of system‐specific assets and risk of franchisee free‐riding, respectively. These hypotheses are tested in the French franchising context by using a sample of 138 franchisors. The empirical results are largely supportive of the hypotheses. We extend the franchising literature by arguing that the explanation of the franchisor's use of multi‐unit franchising requires the combined application of different theoretical perspectives. Copyright © 2012 John Wiley & Sons, Ltd.